Tanggung Jawab Sosial Korporat Terhadap Pekerja Dan Prestasi Ekonomi Syarikat Di Indonesia Dalam Kontek Kesatuan Sekerja - Dina Madinah; Mara Ridhuan Che Abdul Rahman; Mohd Rizal Palil; Shifa Mohd Nor (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 38-47